Fingerprint Based Voting System Using IOT - Snehal Gurav,; Anushka Fase,; Dipali Masal,; Gaurakka Umarani,; K. I. Chouhan, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The “Fingerprint Voting System[3] Using IOT” is an innovative approach to enhancing the security, reliability, and efficiency of the voting process. This system integrates biometric fingerprint recognition with IOT (Internet of Things) technology to create a secure, user-friendly, and tamper-proof voting mechanism. Traditional voting systems are often vulnerable to identity fraud, ballot manipulation, and delays in result compilation. By leveraging fingerprint biometrics, the system ensures that each voter can only cast one vote, thereby eliminating the possibility of voter fraud and multiple voting. The system operates as follows: each voter is required to authenticate their identity through fingerprint scanning before accessing the voting platform. The fingerprint data is matched with a pre-existing voter database to verify eligibility. Once authenticated, the voter is granted access to the digital ballot system, where they can securely cast their vote. The IOT component connects the voting terminals to a centralized server over a secure network, ensuring real-time data transmission and immediate updates to the voting status.
Keywords: IoT; fingerprint Authentication; voting system; biometric security; real-time data processing; secure elections